PENGARUH EFEKTIFITAS PENYULUHAN, PENERAPAN APLIKASI SISTEM ELEKTRONIK PERPAJAKAN DAN PEMERIKSAAN PAJAK TERHADAP TINGKAT KEPATUHAN PEMENUHAN KEWAJIBAN PERPAJAKAN (STUDI PADA KPP PRATAMA SURABAYA WONOCOLO) - Novita, Anastasia Rizqa (Jurnal Mahasiswa Perpajakan, 2014)
Tax is one example of acceptability come from in-country that are very important to finance national development and have a very large role in filling the State Treasury.The purpose of this research was to know influence significant simultaneously or partial variable tax information, the application of application electronic system of taxation and examination taxes on compliance rate fulfillment of an obligation taxation. This research use the kind of research explanatory research with the approach quantitative. A method of analysis used is descriptive analysis and inferential analysis. The population is the Taxpayer listed on the KPP Pratama Surabaya Wonocolo, with samples taken of100 respondents.The results of this research show that the independent variables tax information, electronic system of taxation, and examination taxes, influential simultaneously and partial against dependent variable namely compliance rate fulfillment of an obligation taxation.Tax Information is the most dominant factor in influencing the compliance rate fulfillment of an obligation taxation in KPP Pratama Surabaya Wonocolo. DJP have to evaluate the procedure to electronic system of taxation for giving better service. Key Word : Tax Information, Electronic System of Taxation, Examination, and Compliance Rate Fulfillment of an Obligation Taxation.